2008
DOI: 10.1159/000141901
|View full text |Cite
|
Sign up to set email alerts
|

Geophagy in New World Monkeys (Platyrrhini): Ecological and Geographic Patterns

Abstract: Geophagy has been recorded in an increasing number of New World monkeys (Platyrrhini) over recent years, permitting a tentative analysis of ecological patterns. While geophagy has now been recorded in species representing all 4 platyrrhine families and a majority of genera, there is a marked tendency for it to occur in the larger-bodied Pitheciidae and Atelidae. Howlers (Alouatta) are responsible for almost a third of reports, which are concentrated in the more frugivorous species, Alouatta belzebul and Alouat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…It may be significant, then, that in most long-term studies spider monkeys are reported to feed on clay from mineral licks (Izawa 1993, Link et al 2011a, which is suggested to be one means by which they cope with the effects of secondary metabolites. Spider monkeys at San Juan and elsewhere are also reported to feed on decayed wood from dead standing trees (Suarez 2006, Di Fiore et al 2008, Chaves et al 2012, which may allow them ac cess to additional minerals not otherwise available in their diet (Krishnamani & Ma haney 2000, Ferrari et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…It may be significant, then, that in most long-term studies spider monkeys are reported to feed on clay from mineral licks (Izawa 1993, Link et al 2011a, which is suggested to be one means by which they cope with the effects of secondary metabolites. Spider monkeys at San Juan and elsewhere are also reported to feed on decayed wood from dead standing trees (Suarez 2006, Di Fiore et al 2008, Chaves et al 2012, which may allow them ac cess to additional minerals not otherwise available in their diet (Krishnamani & Ma haney 2000, Ferrari et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Geophagy, the intentional consumption of soil by animals, has been observed in several primate species amongst catarrhines and platyrrhines [Krishnamani and Mahaney, 2000;Ferrari et al, 2008]. For many primate species, or populations, soil is an important and frequently consumed item in their diets (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For many primate species, or populations, soil is an important and frequently consumed item in their diets (e.g. Ateles and Alouat- Folia Primatol 2011;82:25-32 26 Link /de Luna /Arango /Diaz ta ) [Izawa, 1993;Blake et al, 2010;Link et al, 2011] most often obtained from termite mounds, leaf-cutting ant mounds, the forest floor or mineral licks [Ferrari et al, 2008]. Mineral licks are specific sites where not only primates come to eat soil or drink water, but also a large diversity of other mammals and birds use them for similar purposes [Izawa, 1993;Montenegro, 2004;Tobler et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations